One-Year Outcome of Geriatric Hip-Fracture Patients following Prolonged ICU Treatment. (13th January 2016) - Eschbach, Daphne; Bliemel, Christopher; Oberkircher, Ludwig; Aigner, Rene; Hack, Juliana; Bockmann, Benjamin; Ruchholtz, Steffen; Buecking, Benjamin
Abstract : Purpose . Incidence of geriatric fractures is increasing. Knowledge of outcome data for hip-fracture patients undergoing intensive-care unit (ICU) treatment, including invasive ventilatory management (IVM) and hemodiafiltration (CVVHDF), is sparse. Methods . Single-center prospective observational study including 402 geriatric hip-fracture patients. Age, gender, the American Society of Anesthesiologists (ASA) classification, and the Barthel index (BI) were documented. Underlying reasons for prolonged ICU stay were registered, as well as assessed procedures like IVM and CVVHDF. Outcome parameters were in-hospital, 6-month, and 1-year mortality and need for nursing care. Results . 15% were treated > 3 days and 68% < 3 days in ICU. Both cohorts had similar ASA, BI, and age. In-hospital, 6-month, and 12-month mortality of ICU > 3d cohort were significantly increased (p = 0.001 ). Most frequent indications were cardiocirculatory pathology followed by respiratory failure, renal impairment, and infection. 18% of patients needed CVVHDF and 41% IVM. In these cohorts, 6-month mortality ranged > 80% and 12-month mortality > 90%. 100% needed nursing care after 6 and 12 months. Conclusions . ICU treatment > 3 days showed considerable difference in mortality and nursing care needed after 6 and 12 months. Particularly, patients requiring CVVHDF or IVM had disastrous long-term results. Our study may add one further element in complex decision making serving this vulnerable patient cohort.